Metabolic availability of amino acids in humans - Paoletti, Alyssa; Elango, Rajavel; Courtney-Martin, Glenda (Frontiers in Nutrition, 2024)
Knowledge of amino acid bioavailability and the effect of combining complementary protein sources are required to determine how to best meet an individual’s protein and indispensable amino acid needs. Traditionally, protein quality of foods has been assessed using digestibility data. Digestibility may overestimate bioavailability of some amino acids particularly those more susceptible to heat and processing. The indicator amino acid oxidation (IAAO) method has been validated and applied to determine amino acid bioavailability termed metabolic availability of the first limiting amino acid of a proteinaceous food. The metabolic availability of the limiting amino acid in the test protein is determined as a ratio of the indicator amino acid oxidation response to graded intakes of the test protein compared to the indicator response to a reference protein (crystalline amino acid patterned after egg protein). The IAAO method has also been applied to assess the effect of protein complementation directly in humans on the overall protein quality of the diet. The results demonstrate that protein complementation augments the limiting amino acid supply and increases protein synthesis.